Cleaning Service Mobile Application - LING, TI LEE; HAMID ALI, FIRKHAN ALI (Applied Information Technology And Computer Science, 2025)
EasyClean addresses the growing demand for efficient and community-centric cleaning services in Parit Raja. Recognizing the challenges in traditional service models, EasyClean aims to streamline and innovate the cleaning service sector through a mobile application. The project's objective focuses on designing and developing an Android-based mobile application using object-oriented methodology, catering exclusively to Parit Raja residents. The app encompasses cleaning service booking processes, cleaning supplies rental and sharing modules, and integrates a unique, cleaner recruitment component. All tests in the test plan passed except for two, bookings and renting cleaning supplies test, which failed due to payment and banking API issues. While all users in the user acceptance testing found admin functions easy to use, 12.5% reported difficulty navigating the app and accessing income information. Although there are some limitations, EasyClean demonstrates significant potential in enhancing the efficiency and accessibility of cleaning services within the community.